If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4-8e-17=19-4e+7
We move all terms to the left:
4-8e-17-(19-4e+7)=0
We add all the numbers together, and all the variables
-8e-(-4e+26)+4-17=0
We add all the numbers together, and all the variables
-8e-(-4e+26)-13=0
We get rid of parentheses
-8e+4e-26-13=0
We add all the numbers together, and all the variables
-4e-39=0
We move all terms containing e to the left, all other terms to the right
-4e=39
e=39/-4
e=-9+3/4
| (d+2)/3=5 | | 0=z2-z-2 | | (3t-2)/5=6 | | u2-9u+8=0 | | x2+6=x3-2 | | 4g/3=2 | | 7/8t=8/9 | | d/3-5=13 | | -3x+5=6x-14 | | 20=3(2x+1)+7x | | 8n+3/15=15/n | | (x-15)-(2x-10)=2 | | 8x+3=15/8x | | 6x+2(x–3)=4x+x–18 | | x-x^-12=0 | | 2(4z–9–11)=166–46 | | x-√x-12=0 | | 6y+10=53 | | 8n+3=15/8n | | m+4=12=9 | | 8n+3/15=8n | | 8n+3/15=n | | Y+11÷6-x+1÷9=x+7÷4 | | 8n+3=15/n | | 3x^2-100=143 | | 8n+3=15n | | Y+11÷6-y+1÷9=y+7÷4 | | x(x-13)(x+1)=0 | | (3x+4)-(7x-3)=10 | | x0.6=1.2 | | 5/x-5=-4/x+4+9/(x-5)(x+4) | | -16+(m/4)=-3 |